KECEMASAN MATEMATIKA PADA PEMBELAJARAN DARING DI SEKOLAH DASAR - Daswarman Daswarman; Fattah Hanurawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The increasingly rapid spread of the corona virus has had a lot of influence on the world of education. This influence can occur psychologically. One of the effects that occurs is the mathematics anxiety experienced by teachers in online learning. The purpose of this study was to describe the mathematics anxiety experienced by teachers during online learning. The research was carried out with the subject of teachers at SDN 32 Bungo Padang Padang. Descriptive research method with case study design is used in the research. The data collection used in this study was through interviews. Based on the results of the study, it was found that there was teacher anxiety in learning mathematics including students did not understanding the subject matter, assignments did not done independently by students, students studied without parental guidance at home, unsupported learning equipment and available networks. To overcome this anxiety, it is necessary to cooperate between teachers, parents and students so that good results in learning are obtained.